2015
DOI: 10.1139/cjb-2014-0129
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vessel porosity and leaf emergence pattern in ring- and diffuse-porous deciduous trees in a temperate hardwood forest

Abstract: To elucidate the functional relationship between intra-annual variations in vessel diameter and leaf emergence pattern of ring-porous and diffuse-porous deciduous trees in temperate forests, we determined the temporal relationships between leaf phenology and vessel formation. Cylindrical stem cores were periodically collected from each of five ring-and diffuse-porous species, and the leaf and vessel formation were observed simultaneously. In the ring-porous species, vessel formation began within 2 weeks of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies revealed that the timing of vessel formation in relation to leaf appearance in typical ring-porous deciduous species differs from that in typical diffuse-porous species (Ladefoged 1952;Suzuki et al 1996Suzuki et al , 2000Takahashi et al 2013Takahashi et al , 2015. The first-formed vessels, which develop new rings adjacent to the annual ring border, mature around the time of leaf appearance in stems of ring-porous species (Zasada & Zahner 1969;Suzuki et al 1996Suzuki et al , 2000Sass-Klaassen et al 2011;González-González et al 2013;Takahashi et al 2013;Kudo et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies revealed that the timing of vessel formation in relation to leaf appearance in typical ring-porous deciduous species differs from that in typical diffuse-porous species (Ladefoged 1952;Suzuki et al 1996Suzuki et al , 2000Takahashi et al 2013Takahashi et al , 2015. The first-formed vessels, which develop new rings adjacent to the annual ring border, mature around the time of leaf appearance in stems of ring-porous species (Zasada & Zahner 1969;Suzuki et al 1996Suzuki et al , 2000Sass-Klaassen et al 2011;González-González et al 2013;Takahashi et al 2013;Kudo et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…To simulate more precise formation of late wood, improvements can be attempted, specifically in Stage 2. This shortened annual cycle system could also become a useful model system for field studies such as investigating the timing between bud breaking and cambial activity [29][30][31][32], cambial reaction to partial heating [33][34][35] and partial cooling [36] of tree stem. In fact, using a similar system, it was reported that the roots alter their functions depending on the seasons [17,18].…”
Section: Microscopymentioning
confidence: 99%
“…The vessels of diffuse-porous trees can recover from freezing during winter [19,22,23], though they have low water conduction efficiency [19]. Furthermore, ring-porous trees form leaves and vessels synchronously to meet water transport requirements, whereas diffuse-porous trees show asynchronous tissue formation patterns [24]. Unlike diffuse-porous trees, the vessel diameter of ring-porous trees changes with leaf formation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ring-porous trees form leaves and vessels synchronously to meet water transport requirements, whereas diffuse-porous trees show asynchronous tissue formation patterns [24]. Unlike diffuse-porous trees, the vessel diameter of ring-porous trees changes with leaf formation [24]. Takahashi et al [24] published a quantitative analysis of the relationship between vessel formation and leaf expansion after leaf appearance, though it is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation